Pengaruh Meditasi Mindfullness terhadap Perubahan Cemas The Effect of Mindfullness Meditation on Anxiety Changes - Sari, Dewi Keumala; Nababan, Riko Hengki; Daulay, Wardiyah (Jurnal Kesehatan, 2023)
Mindfulness meditation has enormous benefits in the treatment of anxiety and depression symptoms. Mindfulness practice is also associated with improved immune function, decreased psychological distress, improved well-being, reduced anxiety and increased empathy and compassion. Mindfulness practitioners can be happier, more satisfied and healthier, and have a better sense of equanimity compared to non-mindfulness practitioners. There are two types of anxiety, namely state anxiety and trait anxiety, which can affect a person's response to certain situations. The purpose of this literature review is to identify, evaluate, and synthesize the literature on mindfulness meditation and its application to the anxiety. In addition, this review is also aimed to integrate knowledge and experience with literature regarding therapy. The method used was a systematic literature review by analyzing several articles obtained from electronic databases including ProQuest, Google Scholar, and PubMed. The results of the review of ten selected journal articles showed that mindfulness meditation can help reduce anxiety and depression, as well as improve the level of awareness, cognitive function, and emotional memory.